Trait combinations that improve rice yield under drought: Sahbhagi Dhan and new drought-tolerant varieties in South Asia - Anantha, M.S.; Patel, Devraj; Quintana, Marinell; Swain, Padmini; Dwivedi, Jawaharlal L.; Torres, Rolando O.; Verulkar, Satish B.; Variar, Mukund; Mandal, Nimai P.; Kumar, Arvind; Henry, Amelia (Wiley, 2016)
Drought is one of the most severe constraints reducing rice (Oryza sativa L.) yield in rainfed environments. ‘Sahbhagi Dhan’ (IR74371‐70‐1‐1) is a drought‐tolerant rice variety that was released in India in 2010—and subsequently in Nepal as ‘Sukha Dhan 3’ and in Bangladesh as ‘BRRI Dhan 56’—and has performed well in rainfed farmers’ fields. This study was conducted to understand the physiological drought response characteristics of Sahbhagi Dhan that contribute to its increased yield under drought. Physiological characterization of Sahbhagi Dhan and other newer breeding lines was conducted across multiple seasons at one site in the Philippines and at four sites in India. Several distinct traits of Sahbhagi Dhan were observed: high emergence rates under direct‐seeded germination‐stage stress, a high proportion of total root length as lateral roots in some seasons, high harvest index under drought, and high yield stability across wet seasons. However, some unfavorable responses of Sahbhagi Dhan were observed: impaired growth when sown during seasons with early‐stage cold temperatures or low solar radiation, resulting in relatively low yield stability across dry seasons. These results point to the importance of combining multiple traits for yield stability across drought‐prone environments. Some of the newly developed breeding lines showed even greater yield stability than Sahbhagi Dhan, reflecting the effectiveness of ongoing improvement through direct selection for grain yield under drought that has resulted in advantageous combinations of physiological traits to increase yield in farmers’ fields.